FINANCIAL TECHNOLOGY (FINTECH) PADA PERBANKAN SYARIAH: APLIKATIF DAN PERAN - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
The research objective is to find out what applications are used by Bank in implementing Financial Technology and what is the role of Bank Muamalat Indonesia in implementing Fintech. The research method used is qualitative with a case study type. The results 1) The application applied by Bank in implementing Fintech is (a) Mobile banking called